Selection criteria for undergraduate degree at private University - Chai, Christopher Yong Chuan (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Malaysia Higher Education Industry has undergone substantial growth as a result a lot of initiative had been done by the Ministry of Higher Education to enlarge the education industry. However, this expansion led to the Higher Education Institution become more competitive and they struggles compete with each other in order to continue survive in this competitive industry Therefore, this study is conducted to understand selection criteria factors for undergraduate degree at a private university. Besides, this study also done to determine which of the selection criteria factors for undergraduate degree at a private university is the most significance. Using survey questionnaire and quota sampling, three hundred and seventy one students currently study at three private University were selected for this study. The data collected were analysed using descriptive statistic and factor analysis. Results show that student had comparatively high expectation on the fixed University characteristic compare to interaction between University and student and influence of significant person. Research revealed that cost and physical of the University have vital influences toward the decision-making process for fixed University Characteristic; parent and teacher is more important compare to non parent and teacher for influences of significant person; lastly indirect interaction is more important compare to direct interaction for interaction between University and student. The Higher Education Institutions authorities or the marketing department may implement the marketing strategies which focus on the important factor that influence student choosing the private University.